PENGARUH PENGETAHUAN KEWIRAUSAHAAN, MOTIVASI BERUSAHA DAN KEMANDIRIAN USAHA TERHADAP KINERJA PEDAGANG KAKILIMA DI WILAYAH KOTAGEDE YOGYAKARTA - Ani Muttaqiyathun (Optimum: Jurnal Ekonomi dan Pembangunan, 2016)
The purpose of this study was to analyze the influence of knowledge aboutentrepreneurship, motivation abd independence effort seeks to performance pedagang kakilima in the area of Kotagede, Yogyakarta. The research was conducted by taking objects on pedagang kakilima in the area of Kotagede Yogyakarta. To accomplish this study, the multiple regression analysis were used to test the hypothesis put forward.The results showed that there is signifi cant influence entrepreneurial knowledge, motivatin and independence effort seeks to performance pedagang kakilima Kotagede area simultaneously. Partially, the motivation just trying to have significant effect, whereas knowledge of business entrepreneurship and self-reliance is not a statistically significant effect.